2010
DOI: 10.1126/science.1186874
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Control of Spin States in Spin-1 Molecules and the Underscreened Kondo Effect

Abstract: The ability to make electrical contact to single molecules creates opportunities to examine fundamental processes governing electron flow on the smallest possible length scales. We report experiments in which we controllably stretched individual cobalt complexes having spin S = 1, while simultaneously measuring current flow through the molecule. The molecule's spin states and magnetic anisotropy were manipulated in the absence of a magnetic field by modification of the molecular symmetry. This control enabled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
510
3
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 460 publications
(545 citation statements)
references
References 27 publications
(55 reference statements)
19
510
3
13
Order By: Relevance
“…Recent theoretical work [19,45] proposed spin-orbit effects (or more generally magnetic anisotropies) as a possible alternative interpretation for some of these other experiments. We will show however that spin-orbit coupling can be neglected in our particular experiment, which is a crucial requirement [19,45] for the robustness of our observation of Kondo underscreening [18]. Finally, recent experimental and theoretical studies [65,66,67,18,68,69,70] have confirmed several microscopic mechanisms at play in the singlet-triplet quantum phase transition, such as the gate tunable Hund's rule, giving extra strength to our initial interpretation.…”
Section: Experiments In Even Charge Quantum Dots: Gate Control Of Spimentioning
confidence: 99%
“…Recent theoretical work [19,45] proposed spin-orbit effects (or more generally magnetic anisotropies) as a possible alternative interpretation for some of these other experiments. We will show however that spin-orbit coupling can be neglected in our particular experiment, which is a crucial requirement [19,45] for the robustness of our observation of Kondo underscreening [18]. Finally, recent experimental and theoretical studies [65,66,67,18,68,69,70] have confirmed several microscopic mechanisms at play in the singlet-triplet quantum phase transition, such as the gate tunable Hund's rule, giving extra strength to our initial interpretation.…”
Section: Experiments In Even Charge Quantum Dots: Gate Control Of Spimentioning
confidence: 99%
“…The presence of a zero-bias Kondo peak still implies a spin-degenerate ground state, and removing an electron must therefore introduce an additional spin, S 2 , which couples ferromagnetically with S 1 to form a triplet ground state, resulting in a spin-1 Kondo effect. 28,29 That the spin has not changed by more than ±1/2 is consistent with the absense of spin blockade. 27 Note that instead of the usual enhancement of the Kondo peak upon approaching the charge degeneracy point a slight depression is observed near V g = 2.0 V in Fig.…”
Section: From the Clear Observation Of A Zeeman Effect [See Figs 2(dmentioning
confidence: 59%
“…Transition-metal magnetic atoms on insulating surfaces, in particular, Mn, 3,4 Co, 5,6 and Fe, [7][8][9] have been the focus of intensive research in the last few years. These have all partially filled d shells, which are highly localized and responsible for the magnetic moment, and extended s-like electrons, which are responsible for the electron conduction.…”
Section: Introductionmentioning
confidence: 99%